Everybody's Favorite Selected Trumpet Solos - ARNOLD, Jay (ed.) (Amsco Music Publishing Co., 1941)
Include are compositions from the pens of the older masters coupled with a representative group of numbers that show off the possibilities of the trumpet to the greates advantage. Many of the pieces require more proficiency with the instrument and are, therefore excellent material for the developing musician.